RELATIONSHIP AGILITY WITH BALL DRIBBLING SKILLS IN FOOTBALL TEAM SMA N 1 PERANAP DISTRICTOF PERANAP INDRAGIRI HULU - Erick indra indra; Saripin,M.Kes '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstraction: The purpose of this study was to find out about whether there is a significant relationship between agility with Ball Dribbling Skills . The problem in this research is the lack of agility with dribbling skills . This research is a form of study correlations , with a population of Football players at SMA N 1 Peranap District of Peranap Indragiri Hulu , the in this study is the result sampling technique . The sample in this study is the entire population of 24 people. Instruments used in this research is Dodding test run to test agility and drible soccer dribbling skills test for . Then the data is processed with statistical , to test for normality with lilifors test at significance level 0,05α , the proposed hypothesis is agility relationship with dribbling skills.Based on the results of research and data processing using statistical procedures In the study it was concluded that the significant level of 5 % was found r table = 0,404 . Thus the rhitung>rtable or 0.709 >0.404 . This shows that there is a correlation between variables X and Y , it can be concluded that agility has a significant relationship with the herding skills of football , where the obtained thitung 4.711 ttable 1.717, so thitung>ttable consequently Ho is rejected and Ha accepted .         Keywords : Agility , results dribbling skills .